Branching fraction measurement of the decay 𝐵+ →𝜓⁡(2⁢𝑆)⁢𝜙⁡(1020)⁢𝐾+ - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Physical review, 2025)
The branching fraction of the decay 𝐵+ →𝜓⁡(2⁢𝑆)⁢𝜙⁡(1020)⁢𝐾+, relative to the topologically similar decay 𝐵+ →𝐽/𝜓⁢𝜙⁡(1020)⁢𝐾+, is measured using proton-proton collision data collected by the LHCb experiment at center-of-mass energies of 7, 8, and 13 TeV, corresponding to an integrated luminosity of 9 fb−1. The ratio is found to be 0.061 ±0.004 ±0.009, where the first uncertainty is statistical and the second systematic. Using the world-average branching fraction for 𝐵+ →𝐽/𝜓⁢𝜙⁡(1020)⁢𝐾+, the branching fraction for the decay 𝐵+ →𝜓⁡(2⁢𝑆)⁢𝜙⁡(1020)⁢𝐾+ is found to be (3.0 ±0.2 ±0.5 ±0.2) ×10−6, where the first uncertainty is statistical, the second systematic, and the third is due to the branching fraction of the normalization channel.